The impact of four different classes of anesthetics on the mechanisms of blood pressure regulation in normotensive and spontaneously hypertensive rats - Bencze, M; Behuliak, M; Zicha, J (Physiological research, 2013)
Most anesthetics induce characteristic hemodynamic changes leading to blood pressure (BP) reduction but the role of renin-angiotensin system (RAS), sympathetic nervous system (SNS) and nitric oxide (NO) synthesis in this BP reduction is unknown. We therefore studied the influence of four widely used anesthetics - pentobarbital (P), isoflurane (ISO), ketamine-xylazine (KX) and chloralose-urethane (CU) - on the participation of these vasoactive systems in BP maintenance. BP effects elicited by the acute sequential blockade of RAS (captopril), SNS (pentolinium) and NO synthase (L-NAME) were compared in conscious and anesthetized Wistar or spontaneously hypertensive rats (SHR). Except for pentobarbital all studied anesthetics evidenced by diminished BP responses to pentolinium. The absolute pentolinium-induced BP changes were always greater in SHR than Wistar rats. KX anesthesia eliminated BP response to pentolinium and considerably enhanced BP response to NO synthase inhibition in SHR. In both rat strains the anesthesia with ISO or CU augmented BP response to captopril, decreased BP response to pentolinium and attenuated BP response to NO synthase inhibition. In conclusion, pentobarbital anesthesia had a modest influence on BP level and its maintenance by the above vasoactive systems. Isoflurane and chloralose-urethane anesthesia may be used in cardiovascular experiments if substantial BP decrease due to altered contribution of RAS, SNS and NO to BP regulation does not interfere with the respective research aim. Major BP reduction (namely in SHR) due to a complete SNS absence is a major drawback of ketamine-xylazine anesthesia.
Keywords: Anesthetics; Xylazine; isofluran; ketamin; Nitric Oxide Synthase; Rats; Anesthetics, Combined; Urethane; inhibitory ACE; xylazin; Angiotensin-Converting Enzyme Inhibitors; gangliové blokátory; krevní tlak; kombinace anestetik; Hypertension; pentobarbital; Disease Models, Animal; Rats, Wistar; mužské pohlaví; potkani inbrední SHR; Ganglionic Blockers; renin-angiotensin systém; chloralosa; Chloralose; krysa rodu Rattus; Isoflurane; modely nemocí na zvířatech; synthasa oxidu dusnatého; zvířata; Blood Pressure; oxid dusnatý; Nitric Oxide; Pentobarbital; Renin-Angiotensin System; hypertenze; ethyl-karbamát; sympatický nervový systém; Sympathetic Nervous System; potkani Wistar; Ketamine; Rats, Inbred SHR; anestetika; Enzyme Inhibitors; Male; inhibitory enzymů; Animals